Analysis of project management principles with the Scrum framework in systems development: a case study in a public organization - Pinto, Jefferson de Souza; Leme, Reginaldo da Silva (Brazilian Journal of Operations & Production Management, 2024)
Objective: Demonstrate a case study on project management using the Scrum framework in the development of systems for a public organization. Design / Methodology / Approach: The research method used in the Case Study is an exploratory research with a qualitative approach, through data collection, application of a structured questionnaire to Stakeholders, Scrum Master and Product Owner and analysis of the artifacts generated. Results: The work demonstrated the factors that affect the effectiveness application of the Scrum framework, highlighting bad practices and barriers related to the understanding of business and products, which reduce the ability to deliver quality and value, ineffectiveness of the method application. Research limitations: the number of interviewees in the organization, for further analysis in the case study. Originality/Value: while previous studies focus on the application of the Scrum method in private companies, this paper presents a case study from the perspective of a public organization.